2005
DOI: 10.2166/nh.2005.0019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological function of a thin extensive green roof in southern Sweden

Abstract: The runoff from and the water balance of a thin extensive green roof with sedum-moss have been studied. The soil cover is about 3 cm underlain by a thin drainage layer. The water balance is determined on a monthly basis. The runoff from the green roof is much reduced compared to runoff from hard roofs because of evapotranspiration. The annual runoff is rather close to that of natural river basins. Although most rainy days there is no or little runoff from the roof, the highest observed daily runoff values are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
85
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 9 publications
5
85
0
1
Order By: Relevance
“…Environmental benefits included ecological preservation, mitigation of air and water pollution, enhancement of urban hydrology, a decrease of urban heat island effects, a reduction of energy consumption, etc. Furthermore, green roofs were able to significantly reduce storm-water runoff and retain rainfall volume with retention efficiencies ranging from 40% to 80% (Bengtsson et al, 2004); bioretention cells were shown to reduce average peak flows by at least 45% during a series of rainfall events in Maryland and North Carolina (Davis, 2008). Even though the results of available studies are encouraging, more research is needed to precisely assess the impact of LIDs on the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental benefits included ecological preservation, mitigation of air and water pollution, enhancement of urban hydrology, a decrease of urban heat island effects, a reduction of energy consumption, etc. Furthermore, green roofs were able to significantly reduce storm-water runoff and retain rainfall volume with retention efficiencies ranging from 40% to 80% (Bengtsson et al, 2004); bioretention cells were shown to reduce average peak flows by at least 45% during a series of rainfall events in Maryland and North Carolina (Davis, 2008). Even though the results of available studies are encouraging, more research is needed to precisely assess the impact of LIDs on the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Research from Europe and North America has shown that green roofs can significantly reduce stormwater runoff volume and peak flow runoff by retaining rainwater in the growing medium (Köhler et al, 2001;Dunnett and Kingsbury, 2004;Liu, 2004;Moran et al, 2004;Bengtsson et al, 2005;Connelly, 2006). However, the runoff reduction effects of green roofs are strongly related to local climatic conditions, such as precipitation and evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetated roofs make use of otherwise unused roof surfaces; they are appreciated for their aesthetic character, their influence on urban hydrology (Bengtsson, 2005;Bengtsson et al, 2005;Villarreal & Bengtsson, 2005), their assumed effect on energy demand for comfort cooling during summer months (Theodosiou, 2003) and their capacity to reduce urban temperatures (Lazzarin et al, 2005). Vegetated roofs can also function as important habitats for plants and animals in the urban landscape, but this generally requires a particular focus on biodiversity in the design of the vegetation system (Brenneisen, 2003).…”
Section: Introductionmentioning
confidence: 99%